Extracellular vesicles contribute to early cyst development in autosomal dominant polycystic kidney disease by cell-to-cell communication - Carotti, Valentina; van Megen, Wouter H.; Rigalli, Juan Pablo; Barros, Eric R.; Sommers, Vera; Rutten, Luco; Sommerdijk, Nico; Peters, Dorien J. M.; van Asbeck-van der Wijst, Jenny; Hoenderop, Joost G. J. (The FASEB journal, 2023)
Autosomal dominant polycystic kidney disease (ADPKD) is characterized by the formation of fluid-filled cysts within the kidney due to mutations in PKD1 or PKD2. Although the disease remains incompletely understood, one of the factors associated with ADPKD progression is the release of nucleotides (including ATP), which can initiate autocrine or paracrine purinergic signaling by binding to their receptors. Recently, we and others have shown that increased extracellular vesicle (EVs) release from PKD1 knockout cells can stimulate cyst growth through effects on recipient cells. Given that EVs are an important communicator between different nephron segments, we hypothesize that EVs released from PKD1 knockout distal convoluted tubule (DCT) cells can stimulate cyst growth in the downstream collecting duct (CD). Here, we show that administration of EVs derived from Pkd1−/− mouse distal convoluted tubule (mDCT15) cells result in a significant increase in extracellular ATP release from Pkd1−/− mouse inner medullary collecting duct (iMCD3) cells. In addition, exposure of Pkd1−/− iMCD3 cells to EVs derived from Pkd1−/− mDCT15 cells led to an increase in the phosphorylation of the serine/threonine-specific protein Akt, suggesting activation of proliferative pathways. Finally, the exposure of iMCD3 Pkd1−/− cells to mDCT15 Pkd1−/− EVs increased cyst size in Matrigel. These findings indicate that EVs could be involved in intersegmental communication between the distal convoluted tubule and the collecting duct and potentially stimulate cyst growth.